Pengaruh Waktu Pelapisan Ni dan Komposit Ni/SiC Terhadap Kekerasan dan Ketahanan Abrasi AISI 410 Menggunakan Metode Pulsa Elektrodeposisi - Miftakhur Rohmah; Yunita; Moch. Syaiful Anwar; Efendi Mabruri (Jurnal Metalurgi dan Material Indonesia, 2020)
Stator and Rotor Blades often experience abrasion wear failure during the steam turbine operation, primarily due to solid erosion particles. The Ni-SiC composite coating was prepared on steel by pulse electrodeposition to improve the working life of stator blade steel. This study serves to determine the effect of time coating Ni and Ni-SiC composite on SS 410 on hardness and abrasion resistance. Four samples with 7.9756 x 0.8 x 2.54 cm dimensions were pre-treated; thus, coatings were applied to each sample using watts solution (250 g/l Ni2SO4, 45 g/l H3BO3, and 45 g/l NiCl2, and 30 gr SiC, and 0.25 gr C12H25NaO4S). After coated, Sample 1 and 2 with a difference in Ni coating time are 15 and 60 minutes; Sample 3 and 4 with Ni-SiC coating time is 30 and 90 minutes was observed by hardness and abrasion test. The highest hardness (292.8 HVN) and weight loss of abrasion (13 milligrams) were obtained by 60 minutes coating time of Ni and followed 90 minutes coating time of Ni-SiC. The increase in the time coating of Ni and Ni-SiC composite, the level of hardness layer increases. The abrasion resistance value of the composite layers in the four samples did not show a linear increase with an increase in the value of hardness